Inferior central sulcus: variations of anatomy and function on the example of the motor tongue area - Fesl, G; Moriggl, B; Schmid, U.D; Naidich, T.P; Herholz, K; Yousry, T.A (NeuroImage (Orlando, Fla.), 2003)
We wanted to define the position of the primary motor tongue area (MTA) by using functional magnetic resonance imaging (fMRI) to display the MTA in relation to the inferolateral segment of the central sulcus (CS). The anatomy of the inferolateral segment was analyzed in 24 healthy subjects, using the magnetization prepared rapid acquisition gradient echo sequence. The position of the MTA was defined in 11 subjects by using fMRI to identify the sites of maximal activation for each subject in relation to that subject's own CS. The MTA was then displayed in three orthogonal planes, and in lateral surface reformations. The inferolateral segment displayed two distinct curves in 33 of 48 (69%) hemispheres, three curves in 6%, and four curves in 23%. Significant paradigm correlated activations were found in every hemisphere. Thereof 89 local maxima were determined, with 84 (94%) located in the region of the CS. Sixty-seven (80%) of the 84 CS activations lay along the two lowest curves of the CS. In 86% of cases, activations situated in the middle and deep portion of the anterior bank of the CS were encompassed within the three axial sections centered on the cella media of the lateral ventricles. In conclusion, the variability of the inferior CS segment precluded the assignment of the MTA to a specific anatomic configuration. However, the position of the MTA could be approximated by the intersection between the CS and the three axial planes through, just above, and just below the cella media of the lateral ventricles.